Pengembangan Media dan Bahan Ajar Qur’an Hadits Berbasis Multimedia - Fitri Fatimatuh Azzahra; Yanto Maulana Restu; Lutfy Husnian Zaini; Sayidina Ali; Salman Alfarizi (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study was conducted to address the problems of Qur’an Hadith learning that are still dominated by traditional methods, such as lectures and limited learning materials. These conditions lead to low student engagement and less optimal understanding of Qur’anic verses and hadiths. The study aims to describe the development process of multimedia-based Qur’an Hadith learning media and teaching materials, to assess the feasibility of the content and media design, and to identify students’ responses to its use in improving motivation and comprehension. This research employed a descriptive qualitative approach. Data were collected through interviews, observations, documentation, and triangulation techniques. Data analysis was carried out through data reduction, data display, and conclusion drawing, while data validity was strengthened through source triangulation, technique triangulation, and member checking. The results indicate that multimedia-based learning media present Qur’an Hadith materials in a more systematic, engaging, and interactive manner, thereby reducing misconceptions in understanding verses and hadiths. Students showed positive responses because the visual and audio elements helped them comprehend abstract concepts more easily. Teachers also experienced benefits in terms of time efficiency and consistency in material delivery. Overall, multimedia-based learning media proved to be an effective solution for improving the quality of Qur’an Hadith learning in the digital era.   Keywords: digital teaching materials, learning motivation, multimedia, Qur’an Hadith learning